Desarrollo e implementación de un sistema web Para la gestión del programa de atención al Adulto mayor “San Ignacio” del GAD Huaquillas. - Castillo Cañarte, Claudia Katherine (2015)
Care program for the elderly "San Ignacio" sponsored by the gad- Huaquillas which aims to provide comprehensive care and improve the quality of life of older adults, did not have the automation of its processes, why is it has developed and implemented a web system for management and control of technical and medical information for the benefit of the elderly, municipality and community, as well as providing important information to the evaluators bodies such as the MIES. For the development of this web system the PHP programming language (acronym for recursive PHP: Hypertext Preprocessor) was used on Zend Framework, implementing the methodology UWE-UML Development (UML-Based Web Engineering) is a tool for modeling applications used in web engineering, with special attention on the systematization and personalization (adaptive systems) and as Manager PostgreSQL Database (relational DBMS and object-oriented free). The benefits obtained with the development of this system were: Keep updated stock information and medical technical aids to be delivered within the gerontology program. In addition, integrity and data security is guaranteed, the clarity of the design model, the ease of deployment of the system, reducing operating costs, the ability to interact with all stakeholders in procedures and flexibility to allow the system to grow according to the new demands, among other factors. By the above, the development of the system for gerontological control seniors allow the GAD-Huaquillas provide better service and a correct management information and refer to the tools used can say that facilitated the development of project, providing speed, security and availability of information on the web portal implemented.